Pengaruh Perspektif Hukum dan Moral Terhadap Etika Penelitian di Bidang Teknologi: Analisis Dengan Structural Equation Modeling (SEM) - Safa Naura Riyanda; Qomariyatus Sholihah; Wahyudi Kuncoro; Nabilla Vira Sucipto; Nabilah Dzatil Hidayah (Jurnal Industri dan Inovasi (INVASI), 2026)
Rapid technological advancement raises ethical challenges in research, particularly regarding legal and moral aspects. This study examines the effects of legal perspective and moral perspective on research ethics in technology, with research ethics literacy as a mediating variable. A quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed. Data were collected from 100 respondents using a Likert-scale questionnaire and analyzed with SmartPLS.The results indicate that research ethics literacy significantly influences research ethics in technology (β = 0.304; p = 0.002), while moral perspective has a significant direct effect (β = 0.436; p < 0.001). Legal perspective shows no direct effect but significantly influences ethics literacy (β = 0.591; p < 0.001) and indirectly affects research ethics through mediation (β = 0.180; p = 0.003). The model explains 35.5% of the variance in research ethics. These findings highlight the critical role of ethics literacy in bridging legal regulations, moral values, and ethical research practices in technology.Keywords: research ethics; legal perspective; moral perspective; ethics literacy; technology research; SEM-PLS